2015
DOI: 10.1161/circoutcomes.114.001563
|View full text |Cite
|
Sign up to set email alerts
|

Insulin Resistance and Risk of Cardiovascular Disease in Postmenopausal Women

Abstract: Background-Insulin resistance is associated with diabetes mellitus, but it is uncertain whether it improves cardiovascular disease (CVD) risk prediction beyond traditional cardiovascular risk factors. Methods and Results-We identified 15 288 women from the Women's Health Initiative Biomarkers studies with no history of CVD, atrial fibrillation, or diabetes mellitus at baseline (1993)(1994)(1995)(1996)(1997)(1998). We assessed the prognostic value of adding fasting serum insulin, HOMA-IR (homeostasis model asse… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
21
1

Year Published

2016
2016
2024
2024

Publication Types

Select...
9
1

Relationship

0
10

Authors

Journals

citations
Cited by 27 publications
(23 citation statements)
references
References 35 publications
1
21
1
Order By: Relevance
“…However, evidence accumulated from systematic reviews, cross-sectional and prospective cohort studies point in favour of an increased risk of developing CVD among subjects without diabetes presenting insulin resistance, despite some discrepancies between studies. 26 27 Indeed, partly corroborating our findings, Schmiegelow et al demonstrated a significant association in a univariable analysis between CVD risk estimated using the Framingham equation and insulin resistance assessed by the HOMA-IR index in a population of 15 288 postmenopausal US women; but this association became non-significant in multivariable analysis after adjusting for HDL-C. 28 Moreover, Howard et al did not find a significant relationship between insulin resistance and atherosclerosis in African Americans, which on the contrary was significant among Euro-Americans. 29 …”
Section: Discussionsupporting
confidence: 87%
“…However, evidence accumulated from systematic reviews, cross-sectional and prospective cohort studies point in favour of an increased risk of developing CVD among subjects without diabetes presenting insulin resistance, despite some discrepancies between studies. 26 27 Indeed, partly corroborating our findings, Schmiegelow et al demonstrated a significant association in a univariable analysis between CVD risk estimated using the Framingham equation and insulin resistance assessed by the HOMA-IR index in a population of 15 288 postmenopausal US women; but this association became non-significant in multivariable analysis after adjusting for HDL-C. 28 Moreover, Howard et al did not find a significant relationship between insulin resistance and atherosclerosis in African Americans, which on the contrary was significant among Euro-Americans. 29 …”
Section: Discussionsupporting
confidence: 87%
“…Many, but not all, large prospective epidemiologic studies have reported an association between resistance to the metabolic actions of insulin and CV outcomes . In these studies, insulin resistance was estimated using rather crude proxies (typically, fasting plasma insulin concentrations and the HOMA‐IR model), which were measured once at baseline and related to future outcomes.…”
Section: Discussionmentioning
confidence: 99%
“…It is a disease commonly found in women after menopause, where the disease symptoms worsen by estrogen deficiency. 144 Generally, an excessive number of pro-inflammatory type 1 macrophages over anti-inflammatory type 2 macrophages were found in the hearts of diabetic mice. Additionally, an increase in the cell apoptosis, fibrosis, reactive oxygen species production, and cardiac hypertrophy had observed in the hearts of ovariectomized diabetic mice.…”
Section: Nanoparticles As Drug Delivery Agents In the Treatment Of CVmentioning
confidence: 99%